Alcohol consumption and female urinary incontinence: A community-based study in Japan - Lee, Andy; Hirayama, Fumi (Wiley-Blackwell, 2012)
Objectives: To investigate the association between alcohol consumption and urinary incontinence among Japanese women. Methods: A total of 300 women aged 40–75 years were recruited from the community in middle and southern Japan. A validated food frequency questionnaire was given face-to-face to obtain information on dietary intake and habitual alcohol consumption. Urinary incontinence status was ascertained using the International Consultation on Incontinence Questionnaire-Short Form. Results: Among the 298 eligible participants, 82 women (27.5%) experienced urine leakage. The prevalence of alcohol drinking and mean ethanol intake were slightly higher among the incontinent women (39%; 7.1, standard deviation 24.1 g/day) than others without the condition (35.6%; 4.3, standard deviation 10.7 g/day). Relative to non-drinkers, the adjusted odds ratios of urinary incontinence were 1.31 (95% confidence interval 0.74–2.33) for alcohol drinking and 1.69 (95% confidence interval 0.42–6.81) for ethanol intake over 32 g/day, though the increases in risk did not reach statistical significance. Conclusions: Little association is evident between alcohol consumption and urinary incontinence in middle-aged and older Japanese women. Further studies are required to define the role of alcohol as a contributing factor of this distressing condition.